2021
DOI: 10.21203/rs.3.rs-264565/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Functional Oils or Probiotics on Performance and Microbiota Profile of Newly Weaned Piglets

Abstract: The study aimed to evaluate a commercial blend of functional oils based on liquid from the cashew nutshell and castor oil as a growth promoter in newly weaned piglets. A total of 225 piglets, castrated males and females with 28 days of age were randomly distributed in pens with 15 animals composing three treatments and five repetitions. The treatments were: control (without the inclusion of additive), probiotics, or functional oils. The performance was evaluated. At 50 days of age, a pool of fresh feces from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The use of Probiotic in the weaned causes gain in live body weight gain in comparison to the control group. (Vieira et al, 2021) [39] . The Saccharomyces probiotic supplemented in the nursing piglets cause increase daily average daily gain (ADG), promote the beta diversity and the colonization of the Erysipelato, clostridium and Christensenella in the Probiotic supplemented nursing piglets.…”
Section: Improves Growth Ratementioning
confidence: 99%
“…The use of Probiotic in the weaned causes gain in live body weight gain in comparison to the control group. (Vieira et al, 2021) [39] . The Saccharomyces probiotic supplemented in the nursing piglets cause increase daily average daily gain (ADG), promote the beta diversity and the colonization of the Erysipelato, clostridium and Christensenella in the Probiotic supplemented nursing piglets.…”
Section: Improves Growth Ratementioning
confidence: 99%
“…The mechanisms of action of CNSLcastor oil have not been fully elucidated. However, in the face of the challenge caused by coccidiosis, CNSL-Castor oil acts as an immunomodulator [27] and modulator of the intestinal microbiota [28]. CNSL-Castor oil helps maintain the animal's immune systems, eliminate parasites, maintain intestinal balance, and improve animal performance [8,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…This fact was also observed in this study, as there was a reduction in Proteobacteria at 28 d-that is, 14 d after the challenge-compared with that in the control treatment. Previous studies have demonstrated that CNSL-castor oil reduces the abundance of Proteobacteria at times of stress in different animals, whether under coccidiosis in chickens [9] or at weaning in pigs [28]. Conversely, [42] it has been observed that monensin supplementation produced a greater relative abundance of gram-negative bacteria of the phylum Proteobacteria and class Clostridia.…”
Section: Plos Onementioning
confidence: 99%